Perceived status of school-based oral health education (SBOHE) in primary schools in Enugu State (2014)
The study was a cross- sectional survey research, aimed at ascertaining primary school teachers ’perception of status of school -based oral health education (SBOHE) in primary schools in Enugu State. Three research questions and one null hypothesis guided the study. The population for the study was 12,783 teachers in 1,208 governments owned primary schools in the 17 local government areas of Enugu State. A total of640primary school teachers were sampled using multi - stage sampling procedure. A 15-item 4-point scale questionnaire known as School -Based Oral Health Education Questionnaire (SBOHEQ) which was developed by the researcher was used to collect data from the respondents. The instrument was validated by three experts and Cronbach Alpha was used to ascertain the internal consistency of the instrument which yielded an index ofO .81. Mean was used to answer the research questions while the null hypothesis was tested using Z-test at P<.05. The findings revealed that the status of existence of oral health education methods, utilization of oral health education strategies and provision of oral health education materials in primary schools in Enugu State were low, and that it was not dependent on location. Based on the foregoing, a number of recommendations aimed at improving the status of school -based oral health education (SBOHE) in primary schools in Enugu State were put forward, which include that Enugu State Universal Basic Education Board (ESUBEB) should organize periodic workshops and seminars for teachers under their employ.